Sweetened and unsweetened seasoned equity offerings and their impact on creditors' wealth in Malaysia and Australia - Mohd Roslen, Siti Nurhidayah (2017)
Previous research has addressed the question of whether sweetener in Seasoned Equity Offerings (SEO) will cause any shareholders’ wealth changes but not on creditors’ wealth. Prior studies have examined the bondholders’ wealth reactions towards firms’ equity offerings (IPO and SEO) by using tradable bonds data. Few, if none, have studied the wealth creations to creditors in companies with non-tradable debt. This study therefore has tried to fill in the literature gaps by examining the creditors’ wealth effect in response to sweetened and unsweetened SEO in Malaysia and Australia by using probability of default model. In addition, this study also looks into the firm and offerings specific factors that will influence firms’ decisions to issue sweetened and unsweetened SEO and identify if these factors are significant in determining the direction and magnitude of wealth reactions. The first objective employs logit and probit regression model in analyzing the determinants of firms’ choice to issue sweetened and unsweetened SEO. The findings conclude that in Malaysia, firms with high long term debt, overvalued stocks, and lower size of proceeds tend to issue sweetened SEO. In contrast, in Australia, firms with low long term debt, undervalued stocks, high managerial ownership, and high risk will have higher propensity to issue sweetened SEO. The second objective is to examine the shareholders and creditors’ wealth creations in sweetened and unsweetened SEO. It was discovered that in both countries, firms that issue unsweetened SEO will have more negative shareholders’ wealth creations that in sweetened SEO. As for creditors wealth creations, both countries have shown a favourable wealth creations for creditors as firms approaching the announcement year. This second objective is then followed by the test on wealth transfer effect between shareholders and creditors surrounding the sweetened and unsweetened announcement period. In general, the study has found a moderate evidence of wealth transfer effect from unsweetened SEO samples in Malaysia. The last objective is to investigate the determinants of shareholders and creditors’ wealth creations in sweetened and unsweetened SEO. In Malaysia market, most of the changes in shareholders and creditors’ wealth can be explained by the firm specific factors. While, in Australia market, the variations in wealth creations for both stakeholders groups were improved when the offer specific factors were added to the existing models.Overall, the evidence show that the shareholders and creditors’ wealth creation in Malaysia and Australia are leading to almost the same conclusion. Additional equity offerings are generally perceived negatively by stock market, but at the same time, could benefit the creditors as a result of lower financial leverage.